Distance Learning in the Field of Finance and Accounting during Epidemics from Students’ Perspectives: A Sample Study of Finance and Accounting Students at the University of Setif-1 - Zenati , Samia; Lainous , Riyadh (Finance and Business Economies Review, 2023)
This research paper aims to explore the perspectives of Finance and Accounting students at the University of Setif-1 regarding the distance learning model used to teach their subjects during periods of epidemics, especially the COVID-19 crisis. A questionnaire was used for the applied study. In the statistical analysis, the We used the mean, standard deviation, and the one-sample t-test with the SPSS software. According to the results, students perceive that the technical and human resources, as well as the surrounding environmental conditions, are not suitable for implementing distance learning. They also expressed dissatisfaction with the educational content of the distance lessons during the COVID-19 crisis. Additionally, they consider that distance learning is less suitable for teaching financial and accounting subjects .